2001
DOI: 10.1523/jneurosci.21-20-08164.2001
|View full text |Cite
|
Sign up to set email alerts
|

Selective Immunolesions of Cholinergic Neurons in Mice: Effects on Neuroanatomy, Neurochemistry, and Behavior

Abstract: The ability to selectively lesion mouse basal forebrain cholinergic neurons would permit experimental examination of interactions between cholinergic functional loss and genetic factors associated with neurodegenerative disease. We developed a selective toxin for mouse basal forebrain cholinergic neurons by conjugating saporin (SAP), a ribosome-inactivating protein, to a rat monoclonal antibody against the mouse p75 nerve growth factor (NGF) receptor (anti-murine-p75). The toxin proved effective and selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 32 publications
8
91
2
Order By: Relevance
“…Additionally, a few p 75NTR -negative basal forebrain cholinergic neurons located in the ventral pallidum and ventral to the lenticular nucleus were found to be spared by the immunotoxin. This is consistent with earlier findings in rat 31 and mouse 44 and is believed to account for intact cholinergic innervations in the amygdala after 192-IgG-saporin administration.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, a few p 75NTR -negative basal forebrain cholinergic neurons located in the ventral pallidum and ventral to the lenticular nucleus were found to be spared by the immunotoxin. This is consistent with earlier findings in rat 31 and mouse 44 and is believed to account for intact cholinergic innervations in the amygdala after 192-IgG-saporin administration.…”
Section: Discussionsupporting
confidence: 93%
“…Cholinergic MS/DB neurons uniquely express p75 NTR (Berger-Sweeney et al, 2001). Although p75 NTR displays a significantly lower affinity to NGF than do Trk receptors in general, a number of roles have been ascribed to it either acting alone or in synergy with TrkA.…”
Section: Trka Signaling Pathway Mediates Acute Ngf Effect In Ms/db Chmentioning
confidence: 99%
“…Because p75 NTR was implicated in the uptake and retrograde transport of tetanus toxin and its H C fragment in motor neurons [63,64], we reasoned that the same mechanism could also be useful for vector targeting the BFCNs. After all, p75 NTR is strongly enriched in BFCNs in the adult brain, and targeting of cholinergic cells by small peptides or fluorescence probes linked to IgG 192 has been utilized for their labeling and destruction in vivo [22,27,29,30,32,65]. Our data show that conjugation of vectors with antip75 NTR antibody does, indeed, enable targeted expression of GFP-encoding vectors in BFCNs in adult rat brain.…”
Section: Discussionmentioning
confidence: 71%
“…Conjugates of anti-p75 NTR IgG with small fluorescence probes and neurotoxic peptides have been shown to target and facilitate their effects in BFCNs [29,30,48]. Hartig et al [37] also showed that Cy3 bound to IgG 192 selectively labeled BFCNs and stayed within these neurons over several months [37], while IgG 192 conjugates of ribosome inhibitor peptide saporin have been widely used for their lesions [22,27,29,30]. Importantly, neither saporin nor Cy3 linked to IgG 192 hindered its binding to p75 NTR or internalization by BFCNs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation